ANALISIS PENAWARAN DAN PERMINTAAN DAGING SAPI DI INDONESIA SEBELUM DAN SAAT KRISIS EKONOMI: SUATU ANALISIS PROYEKSI SWASEMBADA DAGING SAPI 2005 - KARIYASA, KETUT (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
This research intended to analyze the domestic beef production and demand influence factors and projected for the next ten years forward in relation with the government program for “the meat self-sufficient on 2005”. This research used the national time series data for 1970 to 1999 period. The econometric model (simultaneous regression) approach through the three stage least squares (3SLS) method had been implemented in order to reach the objectives of this research. The analysis of the research results shown that the variables with the economic effects for the domestic of beef production are the beef price it self, interest, population of cows, the price cows and the price of feedstuff. The variables that have the economic effects on the beef domestic demand are the price of beef itself, the price of fishes, the price of eggs, the price of the goat (sheep) meats, income per capita and consumer needs or requests. The elasticity value shown that the beef production just only response to the beef price itself and the cows price variables change. The domestics demand of the beef just only response to the beef price itself and income per capita variables change. The analysis of the research results also shown that the domestics beef production and demand on the economy crisis are 1.3 and 0.5 times lower than before economy crisis. Beside that, the projection results shown that the beef self-sufficient can not be reach, meanwhile on this year, the domestics beef production only 66.8 percent from the total demand.
Keywords: Supply, Demand, Economy Crisis, Beef Self-Sufficient and 3SLS.